A novel programmable attenuator based low Gm-OTA for biomedical applications. (March 2020) - Rajan, V. Senthil; Kishore, K. Hari; Sanjay, R.; Kumaravel, S.; Venkataramani, B.
Abstract: In this paper, a novel programmable operational transconductance amplifier (POTA) using a pseudo resistor based programmable attenuator is proposed. A 4 th order Butterworth programmable low pass filter (LPF) targeted for biomedical applications is designed using the proposed POTA. The proposed POTA and the LPF are designed and implemented in 0.18 ​μm CMOS technology with a supply voltage of 1 ​V and their performances are evaluated through post-layout simulations. The proposed POTA consumes a power of 27 ​nW, and its transconductance could be varied from 27 ​nA/V to 75 ​nA/V. It has higher linearity, dynamic range (DR) of 85.62 ​dB–79.46 ​dB and lower input-referred noise (IRN) of 33.15 μVrms to 58.65 μVrms than pre-input voltage attenuator based OTAs. The proposed LPF consumes a power of 208 ​nW. Its output dynamic range and IM3 lie in the range of (62.1 ​dB–49.26 ​dB) and (61.87 ​dB–53.14 ​dB) respectively. Its cutoff frequency can be varied from 100 ​Hz to 250 ​Hz.